Unveiling the Optical Coherence Tomography Angiography Artifacts - Priyanka Gupta; Daraius Shroff; Charu Gupta (Delhi Journal of Ophthalmology)
Optical coherence tomography angiography (OCTA) is a promising novel method for visualizing the microvasculature of the retina and choroidal vascular layers in the macular area. It provides depth-resolved functional and structural information on blood flow in the vessels. OCTA is based on the principle of motion contrast. Artifacts can arise from optical coherence tomography (OCT) image acquisition, intrinsic characteristics of the eye, eye motion, image processing, and display techniques. There are several algorithms available that have the potential to visualize flow, but all have image artifacts. There are various artifacts like projection artifacts in which images of blood vessels are seen at erroneous locations. Others are motion artifacts, masking, and unmasking. These can be detected by interactive evaluation of the images. To generate a comprehensive assessment, OCTA associated with corresponding enface images and B-scan OCT should be simultaneously evaluated. The goal of this article is to provide a framework for the clinician to understand and recognize OCTA artifacts to reduce the risk of misinterpretation.